Why Coordinated Distributed Experiments Should Go Global. (5th May 2021) - Yahdjian, Laura; Sala, Osvaldo E; PiÑEiro-Guerra, Juan Manuel; Knapp, Alan K; Collins, Scott L; Phillips, Richard P; Smith, Melinda D
Abstract: The performance of coordinated distributed experiments designed to compare ecosystem sensitivity to global-change drivers depends on whether they cover a significant proportion of the global range of environmental variables. In the present article, we described the global distribution of climatic and soil variables and quantified main differences among continents. Then, as a test case, we assessed the representativeness of the International Drought Experiment (IDE) in parameter space. Considering the global environmental variability at this scale, the different continents harbor unique combinations of parameters. As such, coordinated experiments set up across a single continent may fail to capture the full extent of global variation in climate and soil parameter space. IDE with representation on all continents has the potential to address global scale hypotheses about ecosystem sensitivity to environmental change. Our results provide a unique vision of climate and soil variability at the global scale and highlight the need to design globally distributed networks.